Analisis Perkembangan Visual pada Poster Film Trilogi Ant-Man melalui Pendekatan Semiotika Roland Barthes - Muhammad Nabiel Avicenna; Dwi Candra Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Film posters serve as visual communication media that establish a film's identity while conveying meaning through visual elements. This study aims to analyze the visual development of the Ant-Man trilogy posters, consisting of Ant-Man (2015), Ant-Man and the Wasp (2018), and Ant-Man and the Wasp: Quantumania (2023), using Roland Barthes' semiotic approach. This research employed a descriptive qualitative method with documentation as the data collection technique using the official posters of the Ant-Man trilogy. The analysis focused on three visual elements, namely composition, visual hierarchy, and color, which were interpreted through the levels of denotation, connotation, and myth. The findings indicate that the Ant-Man trilogy posters demonstrate a visual development that reflects changes in visual communication strategies and the construction of meaning across each film. This development is reflected in increasingly complex compositions, the evolution of visual hierarchy from a single focal point to a layered structure, and the use of color that adapts to the progression of the narrative. From a semiotic perspective, these changes represent a shift in meaning from individual heroism to collaboration and ultimately to collective heroism in confronting increasingly complex conflicts. These findings suggest that the visual development of the posters not only follows the progression of the film narrative but also functions as a visual communication strategy for constructing identity and meaning throughout the Ant-Man trilogy.